Messy victims and sympathetic offenders: the role of moral judgments in police referrals to restorative justice - Hoekstra, M. S. (Contemporary justice review, 2022)
While restorative justice enjoys increasing popularity in a variety of national contexts, it is not yet a structural part of police work. Implementation is often piecemeal, with only a small minority of cases deemed suitable for a restorative approach. This paper draws on literature on the moral dimensions of street-level bureaucrats’ everyday work to analyse how police officers in the Netherlands decide to (not) refer victims and offenders to restorative interventions. In-depth interviews with police officers who are involved in these interventions show that what they present as pragmatic considerations also involve judgments of the deservingness of victims and offenders. Contrary to the literature on ‘ideal’ victims and offenders of restorative justice, police officers in this study are more likely to offer restorative interventions to ‘messy’ victims – who are seen as partly responsible for the crime due to their behaviour and/or relationship to the offender – and to offenders who are considered pitiable or sympathetic. These judgments partly map unto existing cultural norms and biases, and the resulting selective deployment of restorative interventions may therefore conserve and reproduce inequities in the criminal justice system.